The comparison nonlinearity behaviors of photonic crystal fiber by two reduced lengths of bi-edf in ring cavity - Shahi, Sharifeh; Moghaddam, M.R.A.; Harun, Sulaiman Wadi; Ahmad, Harith (World Scientific Publishing, 2009)
The nonlinearity effects of photonic crystal fiber (PCF) in a ring resonator for different lengths of Bismuth erbium-doped fiber (Bi-EDF) as the Brillouin gain medium is investigated. Bi-EDF (215 cm) itself has high stimulated Brillouin effect at 150 mW that is generated at 1480 nm pump power. The proposed Brillouin fiber laser (BFL) with PCF operates at 1559 nm for 49 cm Bi-EDF, which is upshifted by 0.08 nm from the Brillouin pump with a side-mode suppression ratio more than 12 dB. As a result of using reduced length of PCF and two long Bi-EDF, the BFL is stable at room temperature and compact in this report.